A taste of things to come: Effect of temporal order of information and product experience on evaluation of healthy and sustainable plant-based products - Banovic, Marija; Arvola, Anne; Pennanen, Kyösti; Duta, Denisa E.; Sveinsdóttir, Kolbrún; Sozer, Nesli; Grunert, Klaus G. (Frontiers in Nutrition, 2022)
Current patterns of meat consumption are considered unsustainable. Plant-based products are presented as a solution. However, while some plant-based products thrive, others do not make the cut due to the information “framing” effect issues related to the way how information is presented to the consumers. Information on the nutrition and health properties of food products are usually made available at the point of purchase, but their effect on consumer product evaluation and subsequent purchase intent can also occur later, during or after consumption. This research demonstrates that the effect of nutrition information on product evaluation and purchase intention depends when such information is made available – before first tasting or after first tasting – and that the information interacts with the taste experience in its effect on product evaluation and subsequent purchase intent. Using three plant-based products as an example, we conducted a cross-cultural experimental sensory with temporal order of information as the main between-subject experimental condition (informed before taste vs. informed after taste vs. control condition), and product experience phase (expectation vs. experience vs. post-experience phase) and information content as within-subject conditions. Information content had two levels: lower vs. higher share of oat protein in the product (i.e., source of protein vs. high in protein). The results indicate that information generally increases consumers’ purchase intentions with information before tasting having a higher weight when compared to the condition when information presented after tasting. Presenting the information before tasting also mitigates a drop in the evaluation of taste after tasting, observed in the two other conditions. Further, taste acts as a healthiness cue, but the direction of the inference depends on the availability of health-related information: tasting in the informed condition increased the healthiness perception, whereas tasting in the uninformed condition had the opposite effect. Giving the information before the first tasting also increased the weight of healthiness as compared to taste in the formation of purchase intentions. These findings contribute to a better understanding of the effect of temporal order of information and product tasting have on the consumers’ product evaluations of plant-based products from theoretical and managerial perspectives.